Entrepreneurial Profile of Microentrepreneurs in the States of Mexico and Chiapas (2022)
Entrepreneurial activity is closely related to the economic development of countries, hence the importance of studying it. This research aims to determine microentrepreneurs' entrepreneurial profiles in Mexico to characterize them and find opportunity areas to improve their performance. We use a sample of 409 volunteer microentrepreneurs to whom a questionnaire was applied, with a Likert scale. We analyzed their responses by exploratory factor analysis. The results show that microentrepreneurs in Mexico have an entrepreneurial profile where innovation, creativity, and business vision predominate, as well as the search for updating in new technologies, risk-taking, entrepreneurial passion, and an environmental and social approach. The opportunity areas lie in the use of advanced production and communication technologies to manage their company internally and externally in line with the fourth industrial revolution.